2007
DOI: 10.1093/sleep/30.9.1129
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Biomathematical Model Predictions for Cognitive Performance Impairment in Individuals: Accounting for Unknown Traits and Uncertain States in Homeostatic and Circadian Processes

Abstract: Current biomathematical models of fatigue and performance do not accurately predict cognitive performance for individuals with a priori unknown degrees of trait vulnerability to sleep loss, do not predict performance reliably when initial conditions are uncertain, and do not yield statistically valid estimates of prediction accuracy. These limitations diminish their usefulness for predicting the performance of individuals in operational environments. To overcome these 3 limitations, a novel modeling approach w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 27 publications
(41 reference statements)
0
77
0
Order By: Relevance
“…We assessed indirectly the ability of the metrics to capture the homeostatic and circadian processes by using each metric separately as a dependent variable to fit individual data to the two-process model, which is based on electroencephalography data (Borbé ly, 1982), and has been validated extensively on PVT data (Rajaraman et al, 2008(Rajaraman et al, , 2009Van Dongen et al, 2007). Again, we found that, in general, the RTD metric yielded consistently better fits than the other four PVT metrics, both in terms of the coefficient of determination (R 2 ) and the whiteness of the residual errors (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…We assessed indirectly the ability of the metrics to capture the homeostatic and circadian processes by using each metric separately as a dependent variable to fit individual data to the two-process model, which is based on electroencephalography data (Borbé ly, 1982), and has been validated extensively on PVT data (Rajaraman et al, 2008(Rajaraman et al, , 2009Van Dongen et al, 2007). Again, we found that, in general, the RTD metric yielded consistently better fits than the other four PVT metrics, both in terms of the coefficient of determination (R 2 ) and the whiteness of the residual errors (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…(Note that Bayesian model individualization and forecasting may be applied regardless of the amount of data available; cf. [17]). …”
Section: Bayesian Analysis Of Psychomotor Vigi-lance Lapses (Olofsen)mentioning
confidence: 99%
“…Such approaches, which invariably involve some aspect of Bayesian statistical modeling, utilize a small amount of performance information about the individual at hand, and relate that to the variability in performance profiles previously obtained from a sample of the population (e.g., in a laboratory or field experiment) -see [17]. Given that performance responses to sleep loss involve a trait [7], the performance of a specific individual observed during a sustained operation (i.e., when little or no sleep is obtained), combined with the prior information estimated from the population, allows for reliable prediction of future performance.…”
Section: Introductionmentioning
confidence: 99%
“…The awareness of the increased accident risk in the transport sector, has led to development and use of computerised mathematical process models, dual-models and 3-process models for predicting level of fatigue and its effect on cognitive functions, e.g. alertness/performance in daily life, for navy, airline and railway applications [9][10][11] as well as multimodal fatigue measure assessment for measuring early onset of drivers fatigue [12], but so far these have not been implemented in the fishing industry.…”
Section: Introductionmentioning
confidence: 99%